Alfred Wegener Institute and Old Harbour - Bremerhaven, Germany - Photograph ... - Campbell, Sandy (University of Alberta Library, 2010)
The Alfred Wegener Institute for Polar and Marine Research is located in the brown building in the upper left of the photograph. The Institute's substantial polar library is housed in this building. The ships and U-boat in the Old Harbour are part of the German Maritime Museum (Deutsches Schiffahrtsmuseum) collection. ...